NEW PHARMACOLOGICAL TREATMENTS FOR PATIENTS WITH CHRONIC OBSTRUCTIVE PUMONARY DISEASE (COPD) - Larocca, Nancy Elizabeth; Moreno, Dolores; Garmendia, Jenny Valentina; De Sanctis, Juan Bautista (Biomedical papers, 2011)
Background: Chronic Obstructive Pulmonary Disease (COPD) is a preventable and treatable disease characterized mainly by pulmonary airflow limitation that is not fully reversible. The airflow limitation is usually progressive and associated with abnormal inflammatory response of the lung to noxious particles or gasses. New different pharmacological approaches to decrease inflammation of the airways and consequently disease progression and increase airway obstruction reversibility have been developed.Methods and Results: A literature search using PubMed, Science Direct, EBSCO and free patents on line for the years 2000-2010.Conclusions: Recent discoveries in the physiology and pathology of airways diseases have served to generate potential new drugs for the treatment of COPD patients. Several substances that block or activate specific pathways and receptors the aim of which is to decrease inflammation and increase airway obstruction reversibility are being used in different clinical protocols and hopefully will be available for patients in the near future.
Keywords: COPD/Pharmacological treatment/β agonists/Muscarinic receptor antagonists/Phosphodiesterase inhibitors/NKkb inhibitors/PI3K inhibitors